Arterialisation of the Portal Vein With an Aortoportal Jump Graft for Portal Vein Thrombosis Following Liver Resection for Malignancy - Jiao, Long R. (Hindawi Publishing Corporation, 1999)
Fibrolamellar hepatocellular carcinoma (FHCC) is a variant of hepatocellular carcinoma, which mainly affects a young age group and carries a relatively good prognosis. It is widely accepted that aggressive curative resection is still the best option for FHCC. We report here a case of successful arterialisation of the portal vein with an aortoportal jump graft for portal vein thrombosis, which developed postoperatively in an already comprised portal vein with tumour invasion following an extensive liver resection for FHCC.